Maternal and Neonatal Outcomes in Nulliparous Participants Undergoing Labor Induction by Cervical Ripening Method - Andrikopoulou, Maria; Bushman, Elisa T.; Rice, Madeline M.; Grobman, William A.; Reddy, Uma M.; Silver, Robert M.; El-Sayed, Yasser Y.; Rouse, Dwight J.; Saade, George R.; Thorp, John M., Jr.; Chauhan, Suneet P.; Costantine, Maged M.; Chien, Edward K.; Casey, Brian M.; Srinivas, Sindhu K.; Swamy, Geeta K.; Simhan, Hyagriv N.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development (NICHD) Maternal-Fetal Medicine Units (MFMU) Network (American Journal of Perinatology, 2021)
Objective This study aimed to evaluate maternal and neonatal outcomes by method of cervical ripening for labor induction among low-risk nulliparous individuals.Study Design This is a secondary analysis of a multicenter randomized trial of labor induction at 39 weeks versus expectant management in low-risk nulliparous participants. Participants undergoing cervical ripening for labor induction in either group were included. Participants were excluded for preripening membrane rupture, abruption, chorioamnionitis, fetal demise, or cervical dilation ≥3.5 cm. Cervical ripening was defined by the initial method used: prostaglandin only (PGE; referent), Foley with concurrent prostaglandin (Foley-PGE), Foley only (Foley), and Foley with concurrent oxytocin (Foley-oxytocin). Coprimary outcomes were adverse maternal and neonatal composites. Secondary outcomes included cesarean delivery and length of labor and delivery (L&D) stay. Multivariable analysis was used to adjust for patient characteristics.Results Of 6,106 participants included in the trial, 2,376 (38.9%) met criteria for this analysis. Of these, 1,247 (52.4%) had cervical ripening with PGE, 290 (12.2%) had Foley-PGE, 385 (16.2%) had Foley, and 454 (19.1%) had Foley-oxytocin. The maternal composite outcome was similar among participants who received Foley-PGE (24.1%, adjusted relative risk [aRR] = 1.21, 95% confidence interval [CI]: 0.96–1.52), Foley (21.3%, aRR = 1.16, 95% CI: 0.92–1.45), or Foley-oxytocin (19.4%, aRR = 1.04, 95% CI: 0.83–1.29), compared with PGE (19.7%). The neonatal composite outcome was less frequent in participants who received the Foley-PGE (2.4%, aRR = 0.35, 95% CI: 0.16–0.75) or Foley (3.6%, aRR = 0.51, 95% CI: 0.29–0.89) but did not reach statistical significance for participants who received Foley-oxytocin (4.6%, aRR = 0.63, 95% CI: 0.40–1.01) compared with PGE only (6.8%). Participants who received Foley-PGE or Foley-oxytocin had a shorter L&D stay (adjusted mean difference = −1.97 hours, 95% CI: −3.45 to −0.49 and −5.92 hours, 95% CI: −7.07 to −4.77, respectively), compared with PGE.Conclusion In term low-risk nulliparous participants, Foley alone or concurrent with PGE is associated with a lower risk of adverse neonatal outcomes than with PGE alone. Length of L&D stay was the shortest with concurrent Foley-oxytocin.Key Points
Keywords: induction methods; prostaglandin; Foley; oxytocin; nulliparous